GSM cellular radio telephony - Tisal, Joachim (John Wiley & Sons, 1997)
Thoroughly revised and updated, the second edition of GSM Cellular Radio Telephony, offers guidance through the evolving field of GSM networks. By presenting the GSM standard it describes the varied aspects of this technology including international scale compatibility, spectral frequency usage, availability, adaptability, cost quality, access potentials and proposed services.